Administration and Management of Sport Centre and Sport Science in University - Pongpipat, Sarawut; Tuisri , Parkorn; Rodwattanadisakul , Natcharjarn (Journal of Inclusive and Innovative Education, 2019)
The purposes of this study are to study obstacles of the Sport Centre and Sport Science, in the university, management. This is a qualitative research that applied 3 methods for collecting data; 1) documents 2) in-depth Interview and 3) non-participatory observation. Key persons who provided data in this study are the administrators of the Sport Centre and Sport Science in the universities that are not the administrators in Rajabhat University or Rajamangkala University. The 6 staffs were selected by purposive sampling method; the data collection was analyzed by content analysis method. The results of this study indicated that the Sport Centre and Sport Science in Universities are the organizations that are responsible for service providing, promote and develop physical activities concerning health, exercising, sports and sport sciences, most of them were usually promoted from sport sections/division, student unions and the work plan determined was associated with university’s policy, national sports development plan and educational development plan in undergraduate level. The constraint found is limitation of a budget for organization and system management, the workload was assigned according to organization structure, but it was not covered decision authority to the assigned person, especially financial authority; the administrator is still based on criteria of the organization and applied as a guideline for decision making but the obstacle was found in decision process that required authorization from the committee, this process caused decision delayed. The other problem is recruitment process that is not following the system. Moreover, it was observed in control and supervision that the administrators paid attention on follow up with assessment prior to the operation, during and after the operation but the assessment has been performed inequality because the under supervision staffs have no chance to evaluate their supervisors in return. Therefore, these staffs are tired of assessment.